Perancangan User Experience Aplikasi Presensi Mobile Menggunakan Metode Human Centered Design (Studi Kasus: Universitas Kadiri) - Yudhistira Kurniawan Sutiknyo; Hanifah Muslimah Az-Zahra; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Kadiri University is a private university in Kediri. Currently, the attendance system at Kadiri University is still using manual system. The manual attendance system has several lakes, with manual system, students can manipulate their absences and there is an opportunity for errors in recapitulation of attendance data. From these problems, the authors provide a solution by designing a mobile presence aplication. With this design, the process of attendace data recapitulation become easier for lecturers, students, and academic staff, and this design also can minimize student absences data manipulation. The design process is carried out with a user experience creation approach using human-centered design methods and elements of user experience. The human-centered design method consisted of four stages of the approach, namely specify the context of use, specify needs, design application, and evaluate the design. The process of measuring the usability prototype used the heuristic evaluation method using ten usability heuristic principles. Based on the results of the evaluation, it is known that there were 18 problems in the prototype, H1 related to Visibility of System Status, H2 related to Match Between System and The Real World, H3 related to User Control and Freedom, H4 related to Consistency and Standards, H5 related to Error Prevention, H6 related to Recognition Rathen than recall, H8 related to Aesthetic and Minimalist, and H9 related to Help users recognize, diagnose, and recover from errors. Problem with the highest average value was the problem with U5-1 code, which was the problem because there was no confirmation window for submit attendance.